Methods, Techniques and Tools for Knowledge Management - Eric NEUENFELDT (Communications of International Proceedings, 2023)
Document management, knowledge sharing, and training and development are three techniques for effective knowledge management. These techniques can improve collaboration, communication, and innovation within an organization. By managing knowledge effectively, organizations can create a culture of learning and promote creativity. One way that knowledge management can promote creativity is by providing employees with the tools and resources they need to develop new ideas and solutions. For example, by providing access to training and development programs, employees can acquire new skills and knowledge that can help them approach problems in new and innovative ways. Similarly, by implementing effective document management systems and knowledge sharing practices, organizations can create a collaborative environment where employees can share their ideas and build on each other's work. Overall, effective knowledge management is essential for promoting creativity and innovation within an organization. By leveraging the power of technology and collaboration, organizations can create a culture of learning and discovery that can drive success and growth.
Keywords: knowledge management; document management systems; knowledge sharing; training and development